2013
DOI: 10.1593/neo.13432
|View full text |Cite
|
Sign up to set email alerts
|

Improved Clearance during Treatment of HPV-Positive Head and Neck Cancer through mTOR Inhibition

Abstract: Human papillomavirus (HPV)-related head and neck squamous cell carcinoma (HNSCC) incidence is increasing at a near epidemic rate. We investigated whether the mammalian (or mechanistic) target of rapamycin (mTOR) inhibitor, rapamycin, can be used as a concurrent agent to standard-of-care cisplatin/radiation therapy (CRT) to attenuate tumor lactate production, thus enhancing CRT-induced immune-mediated clearance of this antigenic tumor type. A C57Bl/6-derived mouse oropharyngeal epithelial cell line retrovirally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 55 publications
4
54
0
Order By: Relevance
“…Hence metformin represents an attractive drug candidate to prevent the development of cancer lesions that involved mTOR activity. These include HNSCCs, in which multiple molecular mechanisms converge on the stimulation of mTORC1 and the consequent accumulation of the phosphorylated form of ribosomal protein S6 (pS6) and other mTORC1 targets (10, 11, 27). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence metformin represents an attractive drug candidate to prevent the development of cancer lesions that involved mTOR activity. These include HNSCCs, in which multiple molecular mechanisms converge on the stimulation of mTORC1 and the consequent accumulation of the phosphorylated form of ribosomal protein S6 (pS6) and other mTORC1 targets (10, 11, 27). …”
Section: Resultsmentioning
confidence: 99%
“…Most HNSCC and cervical SCC lesions exhibit strongly elevated activity of the PI3K and mammalian target of rapamycin (mTOR) signaling pathway (10ā€“13). The activation of the mTOR pathway renders these cancers sensitive to the inhibition of mTOR by rapamycin and related rapalogs and new mTOR kinase inhibitors, as revealed in multiple pre-clinical animal models and experimental systems (14).…”
Section: Introductionmentioning
confidence: 99%
“…We found that mTOR inhibitors can also interfere with the prosenescent activity of CT. Currently, mTOR inhibitors are under investigation in clinical studies as anticancer agents and are showing growth-inhibiting effects in preclinical models, including xenografts of HPV-positive cancer cells (41)(42)(43). The antitumorigenic effects of mTOR inhibitors in the clinic have often been unsatisfying when given as a monotherapy, however (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…In regard to HPVā€related oropharyngeal SCC, patients are younger and have a higher lifetime risk for radiation and medicationā€associated complications. Among others, we could show that targeting the PI3K and mTOR axis can lead to enhanced radiosensitivity . Therefore, a potential future application of mTOR or combined AKT/mTOR inhibitors could reduce the radiation dose in HPVā€related oropharyngeal SCC and prevent secondary therapyā€related complications in the long term.…”
Section: Discussionmentioning
confidence: 99%